SOLARPACES 2018: International Conference on Concentrating Solar Power and Chemical Energy Systems 2019
DOI: 10.1063/1.5117693
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of a solar thermochemical reactor for MW scaling-up studies

Abstract: A lab-scale solar reactor, equipped with a porous CeO 2 structure with dual-scale porosity for CO 2 and H 2 O splitting, has been simulated and validated using available experimental results. The validated model was then used to scale-up the geometry to the MW scale and to investigate the benefits in the studied reactor. The larger reactors displayed partially better performance, but their potential was limited by the restricted thickness of the porous structure during scaling-up. This restriction accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The reactor is modeled using a simplified one-dimensional (1D) representation. The obvious benefit of a simplified 1D model is the reduced computational demand compared to geometrically accurate three-dimensional representations of the reactor geometry [18] and even more to simulations with locally resolved RPC structure [19,20]. The simplified model approach allows simulations for a larger number of design and operational parameter combinations.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The reactor is modeled using a simplified one-dimensional (1D) representation. The obvious benefit of a simplified 1D model is the reduced computational demand compared to geometrically accurate three-dimensional representations of the reactor geometry [18] and even more to simulations with locally resolved RPC structure [19,20]. The simplified model approach allows simulations for a larger number of design and operational parameter combinations.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In recent years, computational fluid dynamics (CFD) models have been instrumental in the advancement of fixed bed chemical reactors, which are utilized both as investigative and as optimization tools. , In particle-resolved CFD (PR-CFD) models, realistic particle arrangements are generated primarily through the discrete element method (DEM), ,, and the individual particles are resolved and meshed. Particle sizes and shapes within the packed bed can either be mono- or poly-dispersed in nature, with modern DEM-based beds implementing multiple particle shapes, such as spherical, cylindrical, or Raschig rings. ,,,, PR-CFD models yield key information regarding the interconnected nature of the physicochemical phenomena during operation of the fixed bed system. ,, Specifically, their ability to consider the impact of the geometrical bed structure to predict the interparticle heat and mass transfer yields highly valuable insights for reactor engineering. Fixed bed reactors include different levels of “porosity” (Figure ). The particles (gray spheres in Figure a) are immobile, having interconnected gaps between them, referred to as “interparticle network”, where reagents can flow through.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these pore-scales offers distinct advantages to the porous medium. Specifically, macro-pores allow convective flow to traverse the medium, increasing the effective heat and mass transfer compared to what would be possible solely through intraparticle diffusion. , On the contrary, there is no convection through the micro-pores, and the role of this pore-scale is to maximize the effective surface area and thus the reactivity of the porous medium. , In fact, catalytic porous media with dual-scale porosities have been introduced at different applications to reinforce heat and mass transfer through intraparticle convection. , These can be broken down into porous media with large macro-porosities, above 0.5, and with low macro-porosities, below 0.5. For the latter, Yang et al examined the intraparticle flow phenomena within a porous particle containing 10 nm meso-pores and 0.1 mm macro-pores .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studied power range (0.8 kW to 3.8 kW), the temperature of the CFD model has an error range between -0.3% to 7.15% compared with experiment results. Kyrimis et al [46] numerical studied the scale-up solar thermochemical reactor geometry. The results showed that the scale-up geometry has a benefit for the solar-to-fuel efficiency at the beginning of the reduction but limited due to the thickness of CeO2 RPC.…”
Section: Introductionmentioning
confidence: 99%